2015
DOI: 10.1016/j.chemosphere.2015.06.097
|View full text |Cite
|
Sign up to set email alerts
|

First report of the concentrations and implications of DDT residues in chicken eggs from a malaria-controlled area

Abstract: Highlights No published studies on DDT in chicken eggs from a malaria controlled area  Median and maximum ΣDDT concentrations were 11 000 and 48 000 ng/g wet mass  The maximum residue limit was exceeded 100 times  Calculated acceptable daily intake was not exceeded (3 eggs/week/60 kg bm)  Reductions of DDT in soil ingested by chickens may reduce human intake via eggs ABSTRACT In malaria endemic areas, where DDT is still used for vector control by indoor residual spraying (IRS), concentrations of DDT in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Since then, DDT has been sprayed annually in this area, protecting residents from malaria but also resulting in high exposure and environmental contamination with unknown health consequences (17). For instance, residues of DDT, dichlorodiphenyl dichloroethane (DDD) and dichlorodiphenyl dichloroethylene (DDE) (DDT"s breakdown products) were found in water, sediment, vegetables and tissue samples collected from domestic chickens, wild birds and fish in the Limpopo Province of South Africa (18)(19)(20). Other parts of South Africa also reported high concentrations of DDT in birds (21)(22)(23), bird eggs (23)(24)(25), and fish (26,27).…”
Section: Current Use Of Ddt: Indoor Residual Spraying (Irs)mentioning
confidence: 99%
“…Since then, DDT has been sprayed annually in this area, protecting residents from malaria but also resulting in high exposure and environmental contamination with unknown health consequences (17). For instance, residues of DDT, dichlorodiphenyl dichloroethane (DDD) and dichlorodiphenyl dichloroethylene (DDE) (DDT"s breakdown products) were found in water, sediment, vegetables and tissue samples collected from domestic chickens, wild birds and fish in the Limpopo Province of South Africa (18)(19)(20). Other parts of South Africa also reported high concentrations of DDT in birds (21)(22)(23), bird eggs (23)(24)(25), and fish (26,27).…”
Section: Current Use Of Ddt: Indoor Residual Spraying (Irs)mentioning
confidence: 99%
“…Finally, it is important to note that R 2 s for measured and estimated children’s levels may also account for other environmental and lifestyle factors that are shared between mothers and children. For example, consumption of chicken foraging around the dwelling (Van Dyk et al, 2010) and their eggs (Bouwman et al, 2015) may be related among family members and contribute similarly to maternal and child intake.…”
Section: Discussionmentioning
confidence: 99%
“…In several parts of the world, DDT is still in use for controlling mosquitoes. Bouwman et al ( 2015 ) reported a high concentration of DDT in eggs in the entire village that used DDT for vector control, supporting the contention that consumption of endocrine disruptors through diet affects human health most unconventionally. Meat is an excellent dietary source of proteins, and it also contains some micronutrients such as vitamin B12, iron and zinc.…”
Section: Poultrymentioning
confidence: 95%